Directions for The Development of The Aek Sipitu DAI Tourism Area - Jehezkiel Purba; Andi Sahputra Depari; Elin Diyah Syafitri; Rulliannor Syah Putra (Fakultas Teknik Sipil dan Perencanaan, 2025)
Samosir Regency is an area that is considered one of the tourist destinations located in North Sumatra Province. Its tourism assets are diverse, one of which is the Aek Sipitu Dai tourist attraction located in Sianjur Mula-mula District, Samosir Regency. Aek Sipitu Dai is one of the tourist sites that needs to be developed due to its lack of appeal to tourists, resulting in a low number of visits to this destination. The purpose of this research is to formulate directions for the development of Aek Sipitu Dai Tourism. To achieve this goal, specific objectives need to be established, namely evaluating the physical and environmental conditions using the scoring analysis method, and then formulating development directions for tourism in the Aek Sipitu Dai area using triangulation analysis. After the research was conducted, the results consisted of analysis values of the physical and environmental conditions, each with their respective assessment scales for each variable. To formulate directions for the development of the Aek Sipitu Dai tourism area, the results of the physical and environmental condition analyses are compared using the data source triangulation analysis technique.